PENANAMAN PENDIDIKAN KARAKTER DEMOKRATIS DI PONDOK PESANTREN - Istifadatun Na'imah; Imam Bawani (LP3M Universitas Muhammadiyah Muara Bungo, 2021)
The fading of the democratic attitude of the younger generation caused by the development of science and technology that took place significantly in the era of globalization, making the younger generation who are not ready to face the situation will be carried away by the current of change as it is without choosing what kind of culture is accordance with the nation’s personality. Pesantren is as an Islamic educational institution that existence has been recognized by the State, has an important role in educating students to behave well and democratic, as well as when the students have plunged into the world of society. The purpose of this research is to describe the implementation of democratic character education, the importance of democratic character in students, and the things that support and hinder the implementation of democratic character education at the Putri Walisongo Islamic Boarding School. The research above is discussed using qualitative descriptive research with a phenomenological approach. This research was carried out in march-june 2021 by collecting data through observations, interviews, and documentation. This study resulted in the following findings: 1) the implementation of democratic character planting in PPP Walisongo through the exemplary method/ Uswah Hasanah, habituation, and discipline. These three methods are applied to students' daily activities as well as organizational activities, 2) it is important for students to have a democratic character because democracy is one of the teachings of Islam that is based on the Qur'an and Al- Hadith. This Walisongo cottage has stressing on the Qur'an and Al-Hadith. In addition, in order to realize the goals of national education, 3) Things that support and hinder the implementation of character cultivation are in terms of children, parents, organizational components, facilities and infrastructure, religiosity, and the environment.